Variabilità culturale nel XXI secolo e intersezione tra “Area studies” e Scienze Sociali per la produzione di nuova conoscenza - Filomena Riccardi (Culture e Studi del Sociale)
The present article investigates the new developments and challenges of social sciences and humanities in the era of globalization and underlines the importance of social sciences` intersection with interdisciplinary and transregional collaborative researches of Area studies stressing particular attention on the new developments of Social sciences in some developing and emerging countries such as nowadays China, which plays an important role in the contemporary geopolitical world orders.